Market Integration of Indonesia and Malaysia Crude Palm Oil (CPO) Export Prices (A Vecm Approach) - Amanda Sekar Adyanti; Muhammad Ali Yafi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Crude palm oil (CPO) is a prominent example of a palm oil product. It is a primary export from Indonesia and has the highest export volume globally. The development of world CPO export prices that fluctuate dramatically is followed by the movement of CPO export prices in Indonesia and Malaysia, the central exporting countries. This study will answer two objectives: to analyze the market integration between Indonesian CPO export prices and Malaysian CPO export prices and to see the response and contribution between the two variables. The data collection and analysis of this study were conducted in October 2024. The data in the present study is time series data, incorporating Indonesia and Malaysia's variable CPO export prices for 156 months, encompassing the phase from January 2010 to December 2022. In answering the research objectives using the help of market integration analysis with the VECM model approach, several tests must be conducted, ranging from data stationary, lag optimum, cointegration, and Granger causality. The second research objective employs Impulse Response Function (IRF) analysis tools to examine the impact of price changes and Forecast Error Variance Decomposition (FEDV) to predict the response and contribution between the two variables. The analysis yielded findings that indicated the presence of stationarity in both variables at the initial difference stage and the utilization of a criterion at the third lag. Based on the cointegration test's application, cointegration between the two variables states that a one-way integration relationship occurs in the export price of Indonesian CPO to Malaysia. The outcomes of the VECM method, in both the long and short term, indicate a causal correlation between the export price of Indonesian CPO and Malaysian CPO. The findings of the IRF analysis demonstrate that the export prices of Malaysian and Indonesian CPOs exhibit reciprocal responses to external shocks, both in terms of their prices and those of other market prices. The FEVD results indicate that both markets play a role in influencing CPO export prices.